Hidden Cardiovascular Risk: Arterial Stiffness and Left Ventricular Remodeling as Potential Indicators of Masked Hypertension - Chengjie Zhu; Yanna Lei; Vipin Kumar; Xueling Yue; Qingsong Cui; Xian Wu Cheng (The Journal of Clinical Hypertension)
ABSTRACT Masked hypertension (MH), characterized by normal office blood pressure (OBP) but elevated out‐of‐office readings, carries significant cardiovascular risks comparable to those of sustained hypertension, but remains difficult to detect in clinical practice. This review examines the emerging evidence on screening for MH, highlighting recent findings from the PAMELA study demonstrating the clinical utility of combined vascular and cardiac assessments for the detection of MH. Particularly noteworthy is the observation that patients with both an elevated cardiac‐ankle vascular index (CAVI) and left ventricular hypertrophy (LVH) or concentric remodeling had a 2.3‐fold increased risk of MH, particularly in men, independent of age and antihypertensive treatment. CAVI offers distinct advantages as a screening parameter due to its independence from blood pressure fluctuations during measurement, its established prognostic value for cardiovascular outcomes, and its high reproducibility in primary care. We propose a stepwise screening approach, prioritizing CAVI assessment in patients with normal OBP but multiple cardiovascular risk factors, followed by echocardiographic assessment in those with elevated CAVI values. This strategy may facilitate earlier detection of MH, allowing timely intervention to reduce cardiovascular morbidity and mortality, although further validation in different age groups and cost‐effectiveness analyses are warranted.